Change of termite hindgut metabolome and bacteria after captivity indicates the hindgut microbiota provides nutritional factors to the host - Alom, Most Shormi; Cen, Yijing; Tang, Rui; Chen, Dasong; Dou, Hongliang; Mo, Zhenzuan; Du, He (Frontiers in Bioengineering and Biotechnology, 2024)
The gut-dwelling microbiota is an indispensable part of termites. It is influenced by a series of factors, such as diet and captivity. The objectives of this study were to study the metabolic functions of hindgut microbiota and to investigate the influence of captivity on the hindgut microbiota. The dampwood termite Hodotermopsis sjostedti was reared in the laboratory for six months. We conducted the metabolome analysis of the fat body from the freshly-collected workers (FBF), the hindgut fluid of the freshly-collected workers (HFF), and the hindgut fluid of laboratory-maintained workers. In addition, the 16S rRNA genes were sequenced for the hindgut bacteria from the freshly-collected and laboratory-maintained workers. According to our results, the concentrations of metabolites associated with amino acid biosynthesis, vitamin biosynthesis, fatty acid biosynthesis, and cofactor biosynthesis were higher in HFF compared with that in FBF, suggesting that the hindgut microbiota provides nutritional factors to the host. However, after captivity, the concentrations of metabolites in the hindgut associated with amino acid biosynthesis, nucleotide sugar metabolism, vitamin biosynthesis, and carbon metabolism decreased, while those associated with the steroid hormone biosynthesis and ovarian steroidogenesis increased.Meanwhile, the 16S amplicon study revealed that the abundance of certain bacteria changed after captivity, such as uncultured Termite Group 1 bacterium, Candidatus Symbiothrix dinenymphae, and unclassified Desulfovibrio. Our findings show that captivity influences the hindgut microbiota and shed light on the metabolic potential of the hindgut microbiota.